Influence of the Chemical Structure and Physicochemical Properties of Chitin- and Chitosan-Based Materials on Their Biomedical Activity - Kumirska, Jolanta; Weinhold, Mirko X.; Czerwicka, Małgorzata; Kaczyński, Zbigniew; Bychowska, Anna; Brzozowski, Krzysztof; Thöming, Jorg; Stepnowski, Piotr (IntechOpen, 2011)
None